The Relevance Analysis Of Accounting Information, Corporate Social Responsibility And Leverage As Moderation Variables - Indhung Listyaningrum; Kartika Hendra Titisari; Siti Nurlaela (Universitas Negeri Gorontalo, 2021)
An investor always needs accounting information in determining an investment decision. Accounting information relates to many matters relating to the Company's activities in certain periods. The research aims to test and analyse the relevance of accounting information, corporate social responsibility and leverage as moderation variables. The study population of 11 banking companies registered in the IDX period was 2015 – 2018 with a sample number of 44 observations. This sampling technique uses the purposive sampling method. This research hypothesis test uses multiple linear regression with the Moderated Regression Analyys (MRA) approach. Independent variables in this study are the value of profit, book value, and corporate social responsibility. Leverage as a moderation variable and stock price as the dependent variable. The results of this study show that the value of profit, book value and corporate social responsibility affect the stock price. Leverage as a moderation variable can strengthen the book value relationship to the share price, but it cannot strengthen the value of profit relationship to the share price and corporate social responsibility towards the share price. It can be concluded that the value of profit, book value and corporate social responsibility has the relevance of accounting information value. Leverage as a moderation variable can only strengthen the book value relationship to the share price. The degree of research is expected to increase the amount of data samples to achieve more significant results.